2016
DOI: 10.1016/j.envres.2016.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Particulate air pollution, fetal growth and gestational length: The influence of residential mobility in pregnancy

Abstract: Background It remains unclear as to whether neglecting residential mobility during pregnancy introduces bias in studies investigating air pollution and adverse perinatal outcomes, as most studies assess exposure based on residence at birth. The aim of this study was to ascertain whether such bias can be observed in a study on the effects of PM10 on risk of preterm birth and fetal growth restriction. Methods This was a retrospective study using four pregnancy cohorts of women recruited in Connecticut, USA (N=… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(45 citation statements)
references
References 27 publications
3
42
0
Order By: Relevance
“…As a result, the use of hospital referral region as a surrogate may have helped by accounting for some local mobility both in day-to-day travels and residential moves which occurred within the same delivery hospital referral region. We note that another study on air pollution and fetal growth found that residential mobility did not substantively change effect estimates (Pereira et al, 2016). On the other hand, although we fused model-based exposures to observed monitor records and population-weighted our data to improve accuracy for air pollution measures, the use of average pollutant and temperature exposure across a geographic area as a proxy for residential exposure likely resulted in lower variability and biased our findings towards the null.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…As a result, the use of hospital referral region as a surrogate may have helped by accounting for some local mobility both in day-to-day travels and residential moves which occurred within the same delivery hospital referral region. We note that another study on air pollution and fetal growth found that residential mobility did not substantively change effect estimates (Pereira et al, 2016). On the other hand, although we fused model-based exposures to observed monitor records and population-weighted our data to improve accuracy for air pollution measures, the use of average pollutant and temperature exposure across a geographic area as a proxy for residential exposure likely resulted in lower variability and biased our findings towards the null.…”
Section: Discussionmentioning
confidence: 62%
“…With respect to air pollution, in Connecticut, USA, PM 10 exposures during the second trimester and whole pregnancy period were associated with both SGA and tLBW, independent of residential mobility (Pereira et al, 2016). However, we found no evidence of association of any outcome with PM 10 .…”
Section: Discussionmentioning
confidence: 99%
“…We also cannot access maternal residential history; some mothers could move during pregnancy, leading to exposure misclassification. A recent study, however, found that changes in effect estimates were negligible even after taking account for maternal mobility (44). Second, attention should be paid to some variables (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…For example, maternal residential mobility may introduce measurement error when exposures are assigned based upon address at delivery, 27,28 although a recent study suggests this impact may be limited. 29 For mothers who do not move during pregnancy, the assignment of each birth record to a location at the resolution of census block group potentially introduces exposure misclassification because this location may not well reflect the daily activity pattern of the mother. Although the spatiotemporal modeling framework provides more spatially refined estimates of exposure than using assignment to values at a central site, the 1km grid cannot capture fine-scale gradients below this resolution.…”
Section: Discussionmentioning
confidence: 99%